The emergence of grammar in very-low-birth-weight Finnish children at two years of age*. Issue 2 (20th January 2012) - STOLT, SUVI; MATOMÄKI, JAAKKO; HAATAJA, LEENA; LAPINLEIMU, HELENA; LEHTONEN, LIISA
ABSTRACT: It is not well understood how grammar emerges in very-low-birth-weight (VLBW) children. The main aim of the present study was to gain information on the emergence of grammar in this group at 2 ; 0. The Finnish version of the Communicative Development Inventory was used to collect data from VLBW children ( N = 156) and full-term controls ( N = 146). At a group level, the grammatical skills of the VLBW children were significantly weaker than those of the controls. However, when the effect of lexicon size and premature birth on the emergence of grammar was analyzed in detail, few significant differences were found between the groups. The results suggest that even though grammar emerges more slowly for the VLBW children, it emerges in a manner comparable to that of the controls, when the effect of lexicon size is taken into consideration.